Synthesis of trityl radical-conjugated disulfide biradicals for the measurement of thiol concentration - Liu, Yangping (2011)
[Image: see text] Measurement of thiol concentrations is of great importance for characterizing their critical role in normal metabolism and disease. Low-frequency electron paramagnetic resonance (EPR) spectroscopy and imaging, coupled with the use of exogenous paramagnetic probes, have been indispensable techniques for the in vivo measurement of various physiological parameters owing to the specificity, noninvasiveness and good depth of magnetic field penetration in animal tissues. However, in vivo detection of thiol levels by EPR spectroscopy and imaging is limited due to the need for improved probes. We report the first synthesis of trityl radical-conjugated disulfide biradicals (TSSN and TSST) as paramagnetic thiol probes. The use of trityl radicals in the construction of these biradicals greatly facilitates thiol measurement by EPR spectroscopy since trityls have extraordinary stability in living tissues with single narrow EPR line that enables high sensitivity and resolution for in vivo EPR spectroscopy and imaging. Both biradicals exhibit broad characteristic EPR spectra at room temperature due to their intramolecular spin-spin interaction. Reaction of these biradicals with thiol compounds such as glutathione (GSH) and cysteine results in the formation of trityl monoradicals which exhibit high spectral sensitivity to oxygen. The moderately slow reaction between the biradicals and GSH (k(2) ∼ 0.3 M(-1)s(-1) for TSSN and 0.2 M(-1)s(-1) for TSST) allows for in vivo measurement of GSH concentration without altering the redox environment in biological systems. The GSH concentration in rat liver was determined to be 3.49 ± 0.14 mM by TSSN and 3.67 ± 0.24 mM by TSST, consistent with the value (3.71 ± 0.09 mM) determined by the Ellman's reagent. Thus, these trityl-based thiol probes exhibit unique properties enabling measurement of thiols in biological systems and should be of great value for monitoring redox metabolism.